Attracting International Students' Interest in Mobility and Advanced Study Programs in Indonesia: Case Study of Malaysian Vocational Education Students - Rohendi, Dedi; Kuntadi, Iwa; Suryadi, Dedy; Ana; Muktiarni; Hanapi, Zaliza; Ramadhan, Muhammad Oka; Iskandar, Naufal Nadhif Rabbani (Universitas Pendidikan Ganesha, 2024)
In the context of the global economy, the importance of international exposure for vocational students cannot be overstated. Indonesia, with its abundant educational resources and cultural richness, has yet to tap its potential as a leading destination for international students. This study examines the development and impact of a socialization program to increase Malaysian vocational students’ interest in mobility programs and further study in Indonesia. The participants in this study were university students. Data collection was conducted through an online survey using a pretest and posttest questionnaire instrument. Data were analyzed using the Wilcoxon test to test the hypothesis that there is a significant positive change in student interest and the N-Gain value to determine the magnitude of the increase in interest. The results showed a moderate increase in interest, confirming the important role of prior knowledge and institutional image in the decision-making process. These findings suggest that Indonesian universities need to increase their global visibility through strategic marketing and international collaboration. The implications of this study provide important insights for policymakers, higher education institutions, and other stakeholders in increasing Indonesia’s attractiveness as an educational destination for international students, especially from Malaysia.